Sikalabai: Interpretasi Identitas Perempuan Mentawai dalam Penciptaan Koreografi - Hafizatul Rahmi; Ali Sukri; Ajuoktoza Rovylendes; Ariefin Alham Jaya Putra (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This artwork thesis is entitled “Si Kalabai: Interpretation of Mentawai Women’s Identity in Choreographic Creation”. This work departs from the meaning of the Geilat symbol (Mentawai traditional titti/tattoo) as a representation of identity, social status, and the role of women in the Mentawai indigenous community who adhere to the Arat Sabulungan belief. Women in this culture are seen as important subjects in maintaining the balance of life, but in the broader social reality they still often experience role restrictions and inequality. The creation of this dance work aims to interpret the strength, resilience, and struggle of women through the medium of movement as a form of artistic expression and social reflection. The creative method used refers to the stages of Alma M. Hawkins’ choreography, including data collection and field observation, exploration, improvisation, formation, and evaluation. The results of the creation are realized in an abstract contemporary dance work using five female dancers, which are arranged into three main parts, namely oppression, inner resistance, and self-liberation. Non-representational movement elements, the processing of space, time, and energy, as well as the use of internal and external music are utilized to strengthen the delivery of symbolic meaning. The work of Si Kalabai is expected to be a medium for appreciation and understanding of the identity of Mentawai women while also opening up awareness about the importance of equality and respect for women in social and cultural life.